Relative Phenotypic Performance of Crossbred Chicken as Step in Synthetic Breed Development in Ethiopia: A Review (Indian Journal of Animal Production and Management, 2024)
The present review article aims to provide  and summarize synthesized information regarding  some of economically important traits on  reproductive and productive performance of  crossbred chicken to develop both adaptive and  sustainable breed to the intended beneficiaries.  Growth traits, egg production traits, reproductive  traits and other economically important traits of  crossbred chicken were assessed in comparison to  their counterparts purebred breed both native and  exotic parents. In the majority of crossbreeding  studies, the hybrids surpassed the original native  parental breeds in various traits studied, including  body weight, feed conversion ratio, age at first egg,  egg production, egg weight, and egg mass. The  majority of hybrids achieved sexual maturity at an  earlier age, laid more eggs, and produced a greater  egg mass when compared to local chickens. Eggs  from the hybrids were also heavier than those from  the local chickens in certain crossbreeding  experiments. In overall, crossbred chickens that  combine the blood of exotic and local breeds tend  to perform relatively better than indigenous  chickens, which are typically characterized in low  production due genetics. The frequent production of  F1 crossbred demands in subsequent importation of  exotic parent due to produced offspring chicken are  terminal genetically. Also, the degree of heterosis  retained in the crossbred decreased as generation  increased due recombinant ad segregations  effects. To overcome such problem producing  adaptive and sustainable chicken breed through  synthetic breeding is crucial for developing  countries like Ethiopia.
Keywords: crossbred chicken; synthetic breed development; Ethiopia; growth traits; egg production